Interactions between Aeromonas caviae and Yersinia enterocolitica isolated from a case of diarrhea: evaluation of antimicrobial susceptibility and immune response of infected macrophages - Fernández-Bravo, Ana; Recio, Gemma; Figueras, Maria José (Frontiers in Microbiology, 2024)
Aeromonas species cause a wide spectrum of human diseases, primarily gastroenteritis, septicemia, and wound infections. Several studies have shown that about 40% of these cases involve mixed or polymicrobial infections between Aeromonas spp. and bacteria from other genera. However, the immune response of macrophages in front of the bacteria present in the mixed infections, as well as their impact on antimicrobial therapy, have not been investigated. This study evaluated the cell damage and immune response of the mouse macrophage BALB/c cell line (J774A.1) after performing a single and a mixed infection with a strain of Aeromonas caviae and Yersinia enterocolitica, both recovered from the same fecal sample from a patient with diarrhea. Macrophages cell damage was measured by the release of lactate dehydrogenase (LDH) while the immune response was evaluated studying the expression by RT-qPCR of six relevant immune-related genes. Additionally, the antimicrobial susceptibility pattern of the single and mixed strains in front of seventeen antibiotics was evaluated to determine the potential impact on the infection treatment.Macrophages infected with the mixture of the two strains showed a higher cell damage in comparison with the single infections and the immune-related genes i.e., cytokines and chemokines genes (TNF-α, CCL20), and apoptotic and pyroptotic genes were overexpressed. After infection with the mixed cultures, an increase in the antimicrobial resistance was observed for ciprofloxacin, trimethoprim, chloramphenicol, gentamicin and ertapenem were observed. This study increased the knowledge about the synergetic effect of the bacteria involved in mixed infection and on their potential impact on the treatment and evolution of the infection.